2016
DOI: 10.1111/ppl.12458
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic acid differently impacts ethylene and polyamine synthesis in the glycophyte Solanum lycopersicum and the wild‐related halophyte Solanum chilense exposed to mild salt stress

Abstract: This study aimed to determine the effects of exogenous application of salicylic acid (SA) on the toxic effects of salt in relation to ethylene and polyamine synthesis, and to correlate these traits with the expression of genes involved in ethylene and polyamine metabolism in two tomato species differing in their sensitivity to salt stress, Solanum lycopersicum cv Ailsa Craig and its wild salt-resistant relative Solanum chilense. In S. chilense, treatment with 125 mM NaCl improved plant growth, increased produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 67 publications
5
40
0
1
Order By: Relevance
“…For instance, increased expression of the ERF transcription factor in wheat and tobacco conferred improved tolerance to salinity [74,75], whereas enhanced oxidative stress was detected in the ethylene-insensitive (ein3-1) mutant of Arabidopsis exposed to salt stress [76]. Yet, the involvement of ET in salinity responses in halophytes has been scarcely characterized [77,78]. As indicated in our real-time RT-qPCR analysis, ETR1, a gene coding for one of the ET receptors, was strongly and rapidly induced in response to salt ( Figure 5F).…”
Section: Comprehensive Analysis Of Degs Induced By Salt Stress and Bimentioning
confidence: 99%
“…For instance, increased expression of the ERF transcription factor in wheat and tobacco conferred improved tolerance to salinity [74,75], whereas enhanced oxidative stress was detected in the ethylene-insensitive (ein3-1) mutant of Arabidopsis exposed to salt stress [76]. Yet, the involvement of ET in salinity responses in halophytes has been scarcely characterized [77,78]. As indicated in our real-time RT-qPCR analysis, ETR1, a gene coding for one of the ET receptors, was strongly and rapidly induced in response to salt ( Figure 5F).…”
Section: Comprehensive Analysis Of Degs Induced By Salt Stress and Bimentioning
confidence: 99%
“…Plant growth regulators such as auxins, brassinosteroid, jasmonates and strigolactones play a vital role in connection with the signaling network and the developmental and adaptive phenomena in plants growing under stress [3,26,27]. Salicylic acid (SA), a phenolic growth regulator, fortifies the plant defense against a variety of stresses [28][29][30][31]. Hao et al [32] reported the SA-induced expression of 59 proteins involved in a variety of cell responses and metabolic processes in Cucumis sativus.…”
Section: Introductionmentioning
confidence: 99%
“…In Arabidopsis, SA application suppressed the adverse impact of salt stress by reducing the K + leakage in root tissues and increasing the activity of H + -ATPase [35], which strengthens the Na + /H + exchanger at the plasma membrane and reduces the Na + accumulation in cytosol [65]. SA treatment also reduces lipid peroxidation and may interact with other plant hormones to enhance plant resistance and/or tolerance to salt stress [29,31,36,37].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, this is no exception of the fact that Swarna Sub1A may possess the secondary traits for anti-oxidation expression along with suppression of the growth under water. In general, there is a common observation that exogenous application of SA is manifested into total PA pull in plants (33). SA is interacted in a more complex pathway, particularly under stressful condition with other hormonal or growth regulators.…”
Section: Discussionmentioning
confidence: 99%